Zoonotic Diseases as A Historical Public Health Problem in District Poonch and Its Adjoining Area, Union Territory of Jammu and Kashmir, India. - Dr Rattan Lal (International Journal of Pharma and Bio Sciences, 2022)
The main aim of this study in far flung border area of Poonch on the actual line control of pak- occupied Kashmir is to know the frequent out breaks of diseases, more incidences of Zoonotic diseases, emerging and re-emerging of zoonotic infections in district Poonch and its adjoining areas within objective to understand the magnitude of gravity of major emerging and remerging zoonotic public health problem not only in India but also in different parts of world. This study also deals with various aspects of prevalence of zoonotic diseases in District Poonch and its adjoining areas to provide a necessary background to the readers which shall help in better understanding of diseases like Rabies, Japanese encephalitis, Leishmoniasis, Leptospirosis, Tuberculosis, Dengue fever, Salmonella and E. coli infection etc. which has major public health concern. The result of this study would invite the attention of health, Animal husbandry and allied departments to come up with precautionary measures and to make a platform for researcher’s/budding scientists for detailed studies. The Ebola Zika virus, Lyssavirus, SARS, Nipah and Corona virus etc. have alarmed the whole world. Over the last two decades. There has been considerable change in importance of certain Zoonotic diseases in many parts of the world and in this area also which may be resulting from ecological changes such as urbanization. The Corona virus disease in various parts of the world has served a reminder of existence of infectious disease. Hence early diagnosis, treatment and its prevention is of paramount importance. In order to accomplish the study at grass root level more than two hundred informants were interviewed apart from the Medical Veterinary officers, working in rural and urban areas. A study conducted by author on flying foxes roosting in camps on top of some old eucalyptus trees in Poonch City and adjoining areas reveals the relationship among the flying foxes, domestic animals and humans with respect to the transmission of Pathogens. Here nine villages were chosen in and around conservation area and administered a standard closed questionnaire. More than 1500 people mostly men were interviewed residing there in for rabies and other zoonotic diseases. The data so collected was analysed by score system to know the people knowledge and attitude The correlation between respondents, knowledge and residences were analysed by gamma correlation test clearly reveals the area is virulent in in zoonotic diseases. Besides while reviewing/ evaluating the data in one of the study conducted by Directorate of Health Services Jammu Division and its analyses by Z score in respect of communicable diseases indicates the incidences are maximum and composite score and incidences are on higher side in Poonch and its adjoining area. Special thrust was given to the migratory population irrespective of any gender Para-vets/medicos and local Hakims engaged in traditional treatment of ailments of humans and livestock for many years. It is not surprising that in District Poonch where approximately 90% population lives in rural areas in close contact with large domesticated, wild and semi wild animals and abundance of vectors, low economic conditions, lack of medical care, and the zoonotic diseases assume great public health significance. Hence there is dire need to draw the feasibility of integrating humans, animals an environmental health so that one health approach becomes major element of disease control and prevention strategies.